Pemicu Ketimpangan Pendapatan di Regional Kalimantan Tahun 2015-2020 - Nurhasanah, Laili; Muzdalifah, Muzdalifah (PPJP ULM, 2024)
This research was conducted (1) to determine the effect of economic growth, education, agricultural sector GDRP and mining sector GDRP partially on income inequality in Kalimantan Region; (2) to determine the effect of economic growth, education, agricultural sector GDRP, and mining sector GDRP simultaneously on income inequality in Kalimantan Region; (3) to find out what is the most dominant factor affecting income inequality in Kalimantan Region. This type of research is quantitative research. The data used is secondary data obtained through the Central Agency of Statistics from 5 provinces in the Kalimantan Region for 2015-2020. The analysis technique used is panel data regression with the Eviews 12 analysis tool. The results of this research indicate that economic growth, education, agricultural sector GDRP, and mining sector GDRP have a significant effect on income inequality in Kalimantan Region, both partially and simultaneously. The result also indicates that education is the most dominant factor affecting income inequality in Kalimantan Region.